2020
DOI: 10.3389/fped.2020.00029
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Paediatric Acute Kidney Injury Identified Using an AKI E-Alert Algorithm in Six English Hospitals

Abstract: Objective: Acute kidney injury (AKI) is a significant cause of morbidity and mortality among hospitalised patients. The objectives in this study were (i) to investigate the incidence of AKI using the National Health Services (NHS) AKI e-alert algorithm as a means of identifying AKI; and (ii) in a randomly selected sub-group of children with AKI identified using the algorithm, to evaluate the recognition and management of AKI. Patients and Methods:Retrospective cross-sectional study with initial electronic retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
3
6
0
Order By: Relevance
“…The incidence and the severity of AKI in this study is consistent with other studies of AKI among hospitalized pediatric patients ( 1 , 2 , 10 ). A few studies have demonstrated the poor sensitivity of billing/discharge codes in identifying AKI in pediatric patients, both in the US ( 15 ) and internationally ( 10 , 16 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The incidence and the severity of AKI in this study is consistent with other studies of AKI among hospitalized pediatric patients ( 1 , 2 , 10 ). A few studies have demonstrated the poor sensitivity of billing/discharge codes in identifying AKI in pediatric patients, both in the US ( 15 ) and internationally ( 10 , 16 ).…”
Section: Discussionsupporting
confidence: 91%
“…The incidence and the severity of AKI in this study is consistent with other studies of AKI among hospitalized pediatric patients ( 1 , 2 , 10 ). A few studies have demonstrated the poor sensitivity of billing/discharge codes in identifying AKI in pediatric patients, both in the US ( 15 ) and internationally ( 10 , 16 ). Schaffzin et al examined a cohort of non-ICU pediatric patients exposed to nephrotoxins who developed AKI and found that billing codes identified <50% of AKI episodes ( 15 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The goals of these alert systems are not only to enhance provider awareness but also to reduce AKI severity and duration. However, the benefits of these AKI alert tools remain to be determined [44,45].…”
Section: Community Healthcare Standards For Akimentioning
confidence: 99%
“…The median hospitalization time was significantly longer in participants with stage 3 AKI (stage 1 = 2 [1][2][3][4] days; stage 2 = 4 [3][4][5] days; stage 3 = 7 [5][6][7][8][9][10][11] days; p = 0.031 and with hospital acquired AKI (community acquired = 4 [2][3][4][5][6] days; inpatient 9 (6)(7)(8)(9)(10)(11)] days; p = 0.032).…”
Section: Resultsmentioning
confidence: 97%